C-3C: A structure for high reliability with minimal redundancy for batteries - Savard, Christophe; Sari, Ali; Venet, Pascal; Pietrac, Laurent; Niel, Eric (2016 IEEE International Conference on Industrial Technology (ICIT), 2016)
This paper deals with the structures involving the storage cells of electrical energy and on the reconfiguration of these storage systems. It places the existing structures in a matrix configuration to compare their performances in terms of reliability. Then, a different solution: the C-3C structure, for limiting the redundancy for fault tolerance of the cells is proposed and compared with existing patterns. This new configuration, besides it minimizes redundancy, improves battery reliability and increase reliability of a matrix structure of cells.